2000
DOI: 10.1291/hypres.23.supplement_s67
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of in Vivo Ouabain and Digoxin on Renal Artery Function and Blood Pressure in the Rat

Abstract: To investigate vascular mechanisms in hypertension, we isolated renal arterial rings from rats with ouabain-dependent hypertension and studied their function. In rats infused with ouabain for 5 weeks, systolic and mean blood pressures (BP) were increased relative to controls. Contractions evoked by high KCI solutions were greater in rings from ouabain-infused rats whereas the threshold concentrations and EC50sfor KCI and the peak caffeine contractures were not different. KCI contractures were not affected by 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
68
0
12

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 22 publications
5
68
0
12
Order By: Relevance
“…As previously demonstrated, long-term treatment with ouabain induces the development of a time-dependent hypertension (10,21,23,26,32,45,54) as well as regional changes in the ouabain-sensitive sodium pump activity and expression of the ␣-isoforms (45). This hypertension is also associated with a reduction of phenylephrine-induced contractile activity in the thoracic aorta, but not in caudal arteries, and with an increase in the negative endothelial modulation of the actions of phenylephrine in both arteries (45).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…As previously demonstrated, long-term treatment with ouabain induces the development of a time-dependent hypertension (10,21,23,26,32,45,54) as well as regional changes in the ouabain-sensitive sodium pump activity and expression of the ␣-isoforms (45). This hypertension is also associated with a reduction of phenylephrine-induced contractile activity in the thoracic aorta, but not in caudal arteries, and with an increase in the negative endothelial modulation of the actions of phenylephrine in both arteries (45).…”
Section: Discussionmentioning
confidence: 82%
“…It has been suggested that alterations in the activity of the sodium pump might be involved in the genesis or maintenance of hypertensive states (3, 33). Additionally, the hypertension induced by ouabain treatment has been associated with actions in the central nervous system that increase sympathetic activity by activation of the central renin-angiotensin system and impair the arterial baroreceptor reflex (22, 23) and associated with actions in the periphery that produce changes in responsiveness to contractile agents (10,26,45).In some isolated vascular preparations, acutely administered ouabain, at nanomolar concentrations, can enhance the actions of phenylephrine (43). Higher micromolar concentrations of ouabain induce contractions by a direct action on the vascular smooth muscle and/or by releasing norepinephrine from the perivascular adrenergic nerve endings (35,42).…”
mentioning
confidence: 99%
See 3 more Smart Citations